2022
DOI: 10.1021/acs.jpclett.2c00781
|View full text |Cite
|
Sign up to set email alerts
|

Water as an Intrinsic Structural Element in Cellulose Fibril Aggregates

Abstract: While strong water association with cellulose in plant cell walls and man-made materials is well-established, its molecular scale aspects are not fully understood. The thermodynamic consequences of having water molecules located at the microfibril–microfibril interfaces in cellulose fibril aggregates are therefore analyzed by molecular dynamics simulations. We find that a thin layer of water molecules at those interfaces can be in a state of thermal equilibrium with water surrounding the fibril aggregates beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…An induced increase of fibril crystalline domain indicating fibril coalescence was also experimentally observed by Kuribayashi et al 999 However, water steadily stays between fibrils when the applied temperature is maintained below 76 °C and Chen et al showed that this population of water is in thermodynamic equilibrium as opposed to being kinetically trapped. 1000 This means that interfibrillar water lowers the free energy of the bundle and thus acts as an adhesive. On the other hand, interfibrillar water lowers the friction between fibrils facilitating shear deformation, 1001 contributing to the ductility of cellulose materials.…”
Section: Cellulose Twist In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…An induced increase of fibril crystalline domain indicating fibril coalescence was also experimentally observed by Kuribayashi et al 999 However, water steadily stays between fibrils when the applied temperature is maintained below 76 °C and Chen et al showed that this population of water is in thermodynamic equilibrium as opposed to being kinetically trapped. 1000 This means that interfibrillar water lowers the free energy of the bundle and thus acts as an adhesive. On the other hand, interfibrillar water lowers the friction between fibrils facilitating shear deformation, 1001 contributing to the ductility of cellulose materials.…”
Section: Cellulose Twist In Watermentioning
confidence: 99%
“…Langan et al found that fibril aggregation during thermochemical pretreatment with increased temperature up to 160 °C would cause core water expelling among the fibrils. An induced increase of fibril crystalline domain indicating fibril coalescence was also experimentally observed by Kuribayashi et al However, water steadily stays between fibrils when the applied temperature is maintained below 76 °C and Chen et al showed that this population of water is in thermodynamic equilibrium as opposed to being kinetically trapped . This means that interfibrillar water lowers the free energy of the bundle and thus acts as an adhesive.…”
Section: Analytical Tools To Probe Nanocellulose–water Systemmentioning
confidence: 99%
“…When it comes to the (comparatively) poor performance of plant fiber-reinforced composites when subjected to flexural stresses, a frequently alleged explanation is the lack of cohesion between the lignocellulosic fibers and the thermoplastic matrix [ 9 , 12 ]. Indeed, the macromolecules constituting plant fibers, mainly cellulose, are profusely hydrogen-bonded among themselves and with structural water [ 13 ]. In contrast, hydrophobic plastics such as polypropylene (PP) can neither accept nor donate hydrogen bonds, and the surface of PP is essentially non-polar with low electron donor capacity (1.9 mJ/m 2 ) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…CNFs, consisting of a semicrystalline ordered structure of glucan molecules, are the structural building blocks of trees and plants that form strong and self-supporting hydrogel networks at diminishing concentrations containing as much as 99.99% water. These low-density networks are enabled by the fibrils having a high affinity for water, 22 a high stiffness of ∼100 GPa, 24 and a high aspect ratio of up to 800. 25 These properties result in volume-spanning arrested states, also known as colloidal glasses or gels, if the concentration of these materials increases above a certain threshold or decreases the repulsive interactions between the materials.…”
Section: Resultsmentioning
confidence: 99%
“…This model provides a better understanding and utilization of anisotropic fibrillar hydrogels, such as their mechanical behavior for large deformations, the influence of anisotropy, and how they can be optimized in applications. It also demonstrates the robustness of cellulose networks in wet environments with water as an essential material component, 22 providing insight into the evolutionary origin of cellulose as a turgor envelope for aquatic cells or into the basic understanding of the mechanical properties of the plant cell wall 23 .…”
Section: Introductionmentioning
confidence: 96%